Review of the concept of teaching professional identity (Revista Innova Educación, 2020)
This article aims to collect an approximation to the concept of the teaching professional identity from the conceptualization of other identities that intervene in its construction. The teaching identity is of great importance due to the current situation that education is going through with regard to new ways of seeing the role of the educator in virtuality. The narrative is carried out for this review. A bibliographic search and analysis was carried out in academic search engines, magazines, conferences and seminars; as well as in databases. Relationships and tensions were established between the concepts of identity (personal, cultural, social, professional and teaching). From the results, most of the studies indicate this identity as a non-static quality; however, some authors qualify it in social factors linked to the context. It changes when social and cultural patterns prevail. Most papers cover teacher identity from the initial teacher training, but studies are needed at other stages of the training that allow a deeper understanding of the concept.
Keywords: Teacher identity; training; teaching staff